Understanding variations in user response to social media campaigns: A study of Facebook posts in the 2010 US elections. (June 2017) - Xenos, Michael A; Macafee, Timothy; Pole, Antoinette
Political candidates increasingly have incorporated social media tools like Facebook into their campaigns. Such tools enable supporters to interact directly and easily with campaigns, creating an immediate and relatively informal way for users to respond to candidate messages and publicly display their support. Previous research has explored how campaigns have used social media, or how the use of social media may be related to political engagement. In this study, we provide a systematic analysis of variations in user response to candidate messaging through Facebook. Our results shed new light on the dynamics of online campaigning through social media and engagement with supporters through digital media. Specifically, our findings show that variations in the tone, timing, and content of posts, as distinct from contextual factors, are significantly related to how users respond through "likes" and comments.